1990
DOI: 10.1088/0954-3899/16/7/010
|View full text |Cite
|
Sign up to set email alerts
|

Coherent electromagnetic production of mu and tau lepton pairs in relativistic heavy-ion collisions

Abstract: We calculate the coherent production of muon and tauon pairs in peripheral collisions between nuclei at ultra-relativistic energies. This type of production exhibits a high degree of sensitivity to the electromagnetic structure of the nucleons in the colliding nuclei. The pair cross sections, even at high invariant masses and transverse momenta, are large on hadronic scales, and are governed by the magnitude of the nuclear and nucleon form factors at momentum transfers greater than 1 GeVc-'. We argue that this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 15 publications
4
16
0
Order By: Relevance
“…At RHIC energies, the τ − τ + cross section with no form factor in our work approximately is 5 times lower than in Ref. [27], however, the results with the form factor are close to each other. Our cross section results of μ − μ + rates at RHIC and LHC are about slightly lower than in Ref.…”
Section: Calculations and Tablessupporting
confidence: 75%
See 2 more Smart Citations
“…At RHIC energies, the τ − τ + cross section with no form factor in our work approximately is 5 times lower than in Ref. [27], however, the results with the form factor are close to each other. Our cross section results of μ − μ + rates at RHIC and LHC are about slightly lower than in Ref.…”
Section: Calculations and Tablessupporting
confidence: 75%
“…where the value of 2 is 0.71 GeV 2 [27]. We have observed that the effect of this distribution is negligible.…”
Section: 1604mentioning
confidence: 64%
See 1 more Smart Citation
“…14 In the above equation, f Z (q 2 ) is the form factor of a nucleus which gives the momentum distribution of a proton in the nucleus. 9,27 In this work, we have used The effects of nucleus form factors three different charge distribution as uniform, Gaussian and Wood-Saxon(Fermi) and therefore from these distributions we obtain three different form factors in our calculations. For the uniform charged nucleus, the normalized charged distributions can be written as…”
Section: Formalismmentioning
confidence: 99%
“…The above work was extended to other classes of particles (15)(16)(17) and effects from microstructure in the nuclear currents (18). Generally, electron pair production is not strongly affected by the details of the nuclear currents.…”
Section: H(~c)k(tt') = Iandk(tt')mentioning
confidence: 99%